Antiparkinsonian effects of polyphenols: A narrative review with a focus on the modulation of the gut-brain axis - Wei Zhang; Xiaoyu Dong; Rui Huang (Elsevier, 2023)
Polyphenols, which are naturally occurring bioactive compounds in fruits and vegetables, are emerging as potential therapeutics for neurological disorders such as Parkinson's disease (PD). Polyphenols have diverse biological activities, such as anti-oxidative, anti-inflammatory, anti-apoptotic, and α-synuclein aggregation inhibitory effects, which could ameliorate PD pathogenesis. Studies have shown that polyphenols are capable of regulating the gut microbiota (GM) and its metabolites; in turn, polyphenols are extensively metabolized by the GM, resulting in the generation of bioactive secondary metabolites. These metabolites may regulate various physiological processes, including inflammatory responses, energy metabolism, intercellular communication, and host immunity. With increasing recognition of the importance of the microbiota-gut-brain axis (MGBA) in PD etiology, polyphenols have attracted growing attention as MGBA regulators. In order to address the potential therapeutic role of polyphenolic compounds in PD, we focused on MGBA.